2021
DOI: 10.23919/jsc.2021.0013
|View full text |Cite
|
Sign up to set email alerts
|

Literary Destination Familiarity and Inbound Tourism: Evidence from Mainland China

Abstract: Destination familiarity is an important non-economic determinant of tourists' destination choice that has not been adequately studied. This study posits a literary dimension to the concept of destination familiarity -that is, the extent to which tourists have gained familiarity with a given destination through literature-and seeks to investigate the impact of this form of familiarity on inbound tourism to Mainland China.Employing the English fiction dataset of the Google Books corpus, the New York Times annota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 68 publications
0
5
0
Order By: Relevance
“…However, many researchers have expressed their concern about using the single-dimension construct measurement of familiarity which they feel is not appropriate in the temporal tourism environment ( Jebbouri et al, 2021 ; Ju et al, 2021 ). Kim et al (2019) argued that destination familiarity can be enhanced not only by direct experience, but also by indirect experience without actual travel experience.…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, many researchers have expressed their concern about using the single-dimension construct measurement of familiarity which they feel is not appropriate in the temporal tourism environment ( Jebbouri et al, 2021 ; Ju et al, 2021 ). Kim et al (2019) argued that destination familiarity can be enhanced not only by direct experience, but also by indirect experience without actual travel experience.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Nevertheless, researchers have criticized the measurement of the single-dimension construct of destination familiarity, noting that is not appropriate in the temporal tourism environment ( Stylidis, 2020 ; Ju et al, 2021 ). According to Kim et al (2019) , destination familiarity can be increased by direct experiences, such as purchasing and usage behavior, while indirect experience can also significantly influence the familiarity of a tourist with a given destination; this can include exposure to advertisements, reviews from others, the geographic distance between origin and destination, having received information regarding a given destination, perceived knowledge related to education, media coverage, travel guides, social media, and personal contact with others ( Kim et al, 2019 ; Chi et al, 2020 ; Stylidis, 2020 ; Ju et al, 2021 ). Researchers have therefore suggested that two aspects of destination familiarity should be operationalized: experiential and informational ( Kim et al, 2019 ).…”
Section: Theoretical Background and Hypothesis Developmentmentioning
confidence: 99%
“…The results of many studies have demonstrated that destination familiarity based on past travel experience significantly affects the travel decision-making process of visitors ( Prentice, 2006 ; Tan and Wu, 2016 ), but visitors can still attain a definite level of destination familiarity via indirect experience ( Chi et al, 2020 ). Other means of direct experience in creating destination familiarity have largely been overlooked in tourism literature ( Ju et al, 2021 ).…”
Section: Theoretical Background and Hypothesis Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile, SN as an external source also can affect one's perceptions and feelings of ability to perform certain behaviours due to a tourist's perceptions of a product or service greatly influenced by his or her cognitive and affective components (Stylidis et al, 2020). A tourist's perceived ability to visit a destination is highly based on his or her initial knowledge and images of that place (Ju et al, 2021), SN or contact with others as indirect received information can significantly influences one's knowledge, perceptions and feelings of ability to choose a tourism destination (Stylidis et al, 2020). Numerous empirical studies also demonstrated how SN positively influences attitude (Wang et al, 2022b; and PBC (Dinc, Budic, 2016;Wang et al, 2022c).…”
Section: Subjective Norm (Sn)mentioning
confidence: 99%